2016
DOI: 10.3168/jds.2016-11084
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity in calves decreases substantially during the first 3 months of life and is unaffected by weaning or fructo-oligosaccharide supplementation

Abstract: Veal calves at the age of 4 to 6 mo often experience problems with glucose homeostasis, as indicated by postprandial hyperglycemia, hyperinsulinemia, and insulin resistance. It is not clear to what extent the ontogenetic development of calves or the feeding strategy [e.g., prolonged milk replacer (MR) feeding] contribute to this pathology. The objective of this study was therefore to analyze effects of MR feeding, weaning, and supplementation of short-chain fructo-oligosaccharides (FOS) on the development of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In obese dogs and horses, for example, supplementation of dietary scFOS for a period of 6 wk increased insulin sensitivity (Respondek et al, 2008;Respondek et al, 2011). In young veal calves (<3 mo old), supplementation of scFOS for 10 wk did not improve insulin sensitivity or glucose homeostasis (Pantophlet et al, 2016b). In older veal calves (10-13 wk old), however, scFOS supplementation did improve postprandial glucose homeostasis (Kaufhold et al, 2000).…”
Section: Short Communication: Supplementation Of Fructo-oligosaccharimentioning
confidence: 98%
“…In obese dogs and horses, for example, supplementation of dietary scFOS for a period of 6 wk increased insulin sensitivity (Respondek et al, 2008;Respondek et al, 2011). In young veal calves (<3 mo old), supplementation of scFOS for 10 wk did not improve insulin sensitivity or glucose homeostasis (Pantophlet et al, 2016b). In older veal calves (10-13 wk old), however, scFOS supplementation did improve postprandial glucose homeostasis (Kaufhold et al, 2000).…”
Section: Short Communication: Supplementation Of Fructo-oligosaccharimentioning
confidence: 98%
“…This might be attributed to multiple factors: 1] the small number of calves used in this study 2] possible differences in the metabolic profiling techniques used, and 3] possible differences in degree of the experimental contrasts in insulin sensitivity between human and calf studies. In veal calves, insulin sensitivity decreases substantially within the first weeks of life [5], which leads to smaller contrasts in insulin sensitivity in later life. One possible source of variation that can be excluded from subsequent studies is the use of multiple dietary treatments.…”
Section: Discussionmentioning
confidence: 99%
“…These problems have been identified in heavy (4–6 months old) veal calves [13]. In addition, a substantial decrease in insulin sensitivity is observed in calves during the first months of life [4, 5]. In a recent study with heavy veal calves raised on a high-fat or high-lactose MR diet we observed that insulin sensitivity values were low (averaging 4.2 ± 0.5 x 10 −2 [(mg/(kg*min))/(μU/mL)]), and 50% of the calves develop insulin resistance (when comparing insulin sensitivity values with human cut-off values for defining insulin resistance; [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite the low insulin sensitivity in heavy calves, glucose is virtually completely oxidized, regardless of the level of feeding (van den Borne et al, 2007). In addition, insulin peaks in calves typically follow, rather than precede glucose peaks postprandially (Vicari et al, 2008b), even in young calves (MacPherson et al, 2016;Pantophlet et al, 2016b), which differs from responses in other species and illustrates the absence of cephalic responses to a meal. Hence, insulin sensitivity appears not to be a promising target for early life metabolic programming in calves.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 95%
“…It should be noted that the FSIGT test was performed only after a 5-h fasting period, at which point both glucose and insulin concentrations may still have been elevated. Recently, it was demonstrated that in calves, insulin sensitivity decreases rapidly, by almost 70%, between wk 3 and 6 of age, unaffected by weaning (Pantophlet et al, 2016b). It seems therefore that insulin sensitivity in calves is quite high at birth, and decreases independent of feeding strategy in early age to very low levels when compared with other species.…”
Section: Glucose Metabolism and Insulin Sensitivitymentioning
confidence: 99%